Analisis Trend Saham LQ-45 selama Pandemi Covid-19 dengan K-Means Clustering - Prima Hanjasto (SAFE-Network, 2022)
Stocks are one of the investment instruments that have great risks and benefits. Large profits in a very fast time often make investors forget about the risks that may occur. Dynamic price changes at any time require in-depth analysis to determine the decision to buy, hold or sell. The COVID-19 pandemic has had a major effect on economic growth, investment and culture. This study aims to group stocks that have the same trend during the pandemic so that they can get returns and minimize the risk of loss. The stock price data in this study is sourced from finance.yahoo.com with a time span from 2019 to 2021. The stocks to be analyzed are stocks belonging to the LQ-45 stock category from 2019 to 2021. will be grouped with K-means Clustering. This study groups LQ-45 stocks into 3 clusters which are the right considerations by investors in stock investments during the Covid-19 pandemic.